Por qué no necesariamente debería sancionarse una conducta investigada bajo la prohibición general del régimen de competencia? : una propuesta basada en los bienes jurídicamente protegidos (2020)
The general antitrust clause allows the authority to investigate and sanction all those behaviors that threaten healthy competition, without these necessarily being expressly described in the regulation. Protected by this, it has given rise, in recent years, to the imposition of strong limitations against companies, leading to a question about their relevance and conduct. Through a systematic analysis of national norms, doctrine and precedents and foreign comparative law, this article aims to demonstrate that, and if the behaviors that are investigated under the general prohibition norm, grow from the suitability to affect the purposes that the Law aims to protect, the authority may not repress them as anti-competitive practices. As regards, when the general prohibition is interpreted as proposed, the analyzed behaviors are not required and must be sanctioned.